Kadar Air Susu yang Menyebabkan Saudara Sepersusuan (Telaah Ma'ani al-Hadits) - Anisah, Bunga Putri (Jurnal Riset Agama, 2022)
Several themed hadith were found to determine the milk content that caused mahram. With such gifts, some scholars also disagree with their arguments. Hence, researchers were intrigued by the study of hadis-hadith on radha 'ah, a specialty in determining milk content. The study aimed at learning about the hadith content of milk content that caused you to drop down in the study of ma 'anil hadis. The study includes a qualitative kind by applying library or library search by invoked the methods of rij hadis and ma 'anil hadis by applying the al-jam 'u. As for the end result of this study, six hadith found among them the history of the milk of mahram, ath-tirmidzi, and ahmad, which of the hadith divided into four themes of one or two uptake does not make mahram, five breaths can make mahram, childhood reduction, and hunger reduction. The quality of the hadith is shahih, both from sanad and. Scholars also vary in determining the level of compilation that made mahram, this is based on the hadis-hadith of the prophet Saw. As for the ultimate hadith, it is to be a mahram with five breaths, both in terms of both sanad and matan.